がんサバイバーの痛み緩和 - 土田, 陸平; 横島, 弥栄子; 穂積, 淳; 住谷, 昌彦; 水枝谷, 一仁; 阿部, 博昭; 住谷, 瑞穂 (Tairyoku kagaku. Japanese journal of physical fitness and sports medicine, 2018)
From the start, World Health Organization has proposed that palliative medicine is applicable early in the course of illness. However, regrettably, palliative care has been usually provided to patients in the advanced cancer stage, as a terminal care. Recently, palliative medicine begins at the time-point when patients are diagnosed with cancer. In response to change in clinical settings of palliative medicine, cancer pain management has also changed. Considering long-term cancer treatment periods and increasing numbers of cancer survivors, cancer pain management should be recommended based on not only non-opioid pharmacotherapy but also the exercise/rehabilitation medicine and the cognitive-behavioral therapy. Especially, the exercise/rehabilitation medicine can provide beneficial effects on both pain management and cancer treatment itself: Sarcopenia is closely associated with poor prognosis of cancer and debilitating complications of chemotherapy. Further, non-sarcopenia patients can maintain their quality of life higher and show less fatigue during cancer treatment periods. To accomplish such favorable effects for cancer patients and cancer survivors, cancer pain should be managed adequately.